Determination of avian influenza virus H5N2 infection in chicken innate immune cells - Mohd Zaini, Farhana; Abdolmaleki, Mostafa; Yeap, Swee Keong; Tan, Sheau Wei; Ideris, Aini; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Infection with low pathogenic avian influenza virus in birds and mammals is not severe and usually give a mild clinical signs comparing to the highly pathogenic avian influenza virus. Once the virus enter the immune system of an organism, the first defense mechanism which consist of the antigen presenting cells and NK cells will react on the virus by activating the innate and adaptive immunity system. N2 gene from H5N2 strain A/duck/Malaysia/8443/04 was detected using SYBR Green real-time PCR from the infected bone marrow dendritic cell, macrophage and also natural killer cells. Comparing the increment of viral load among 6h, 12h and 24h, there were no significant difference between the viral load detected in bone marrow dendritic cells and natural killer cells. Meanwhile, for macrophage the viral load decreased gradually over time.